Essays on irrational investors’ behavioral biases and pricing efficiency - Klemola, Antti (Vaasan yliopisto, 2019)
This thesis analyzes the effect that investors’ sentiment and overconfidence have on asset prices. Five interrelated essays examine the effect that the changes in U.S. small investor sentiment or the potential overconfidence of market participants in Nordic financial electricity market have on asset prices. The three first essays analyze the effect of changes in irrational investors’ sentiment on future U.S. equity market returns, both on the aggregate and cross-sectional level. The essays employ information from Google search volumes as a potential tool to gauge a new U.S. small investor sentiment. The first essay finds that increase in positive (negative) information retrieval in Google is associated with positive (negative) future returns on the S&P 500 index. The second and third essays find that positive (negative) unexpected changes in the new U.S. small investor sentiment predict not only positive (negative) future U.S. equity market returns, but also positive (negative) subsequent size and value premiums. The fourth and fifth essays examine the effect of investors’ potential overconfidence on option pricing in the Nordic financial electricity market. The fourth essay finds that the market participants are willing to overpay ex-ante for certain type of option contracts. The fifth essay also finds a seasonality effect in the ex-ante pricing of option con-tracts. Both, the investors’ willingness to overpay and the seasonality in the ex-ante pricing of option contracts, might suggest that the irrational investors are overconfident about the precision of their private information.

Väitöskirjan viisi esseetä käsittelevät sijoittajien sentimentin sekä liiallisen itsevarmuuden vaikutusta arvopapereiden hintoihin. Tutkimuksissa analysoidaan amerikkalaisten piensijoittajien sentimentin muutosten tai Pohjoismaiden sähköpörssin markkinaosapuolien liiallisen itsevarmuuden potentiaalisia vaikutuksia arvopapereiden hintoihin. Ensimmäisessä kolmessa esseessä analysoidaan irrationaalisten sijoittajien sentimenttimuutosten yhteyttä Yhdysvaltojen osakemarkkinoiden tuleviin tuottoihin, hyödyntämällä informaatiota Google-hakusanoista. Ensimmäinen esseen tulokset osoittavat, että kasvu positiivisessa (negatiivisessa) tiedonhaussa ennakoi positiivisia (negatiivisia) odotettuja tuottoja S&P 500 -indeksille. Toisessa ja kolmannessa esseessä havaitaan, että positiivinen (negatiivinen) odottamaton muutos amerikkalaisten piensijoittajien sentimentissä ei ennakoi pelkästään osakemarkkinatuottoja Yhdysvalloissa, vaan niillä on myös positiivinen (negatiivinen) yhteys tuleviin koko- ja arvopreemioihin Yhdysvaltojen osakemarkkinoilla. Neljännessä ja viidennessä esseessä tutkitaan sijoittajien liiallisen itsevarmuuden potentiaalista vaikutusta Pohjoismaisen sähköpörssin hinnoitteluun. Neljännessä esseessä tulokset osoittavat, että sijoittajat ovat valmiita maksamaan ylihintaa tietynlaisista optioista. Viidennen esseen tulokset osoittavat lisäksi, että optioiden ylihinnoittelussa esiintyy myös kausivaihtelua. Tietynlaisten optioiden ylihinnoittelu sekä kausivaihtelu voivat viitata siihen, että sijoittajat ovat liian itsevarmoja heidän yksityisen informaationsa tarkkuudesta.
Irrationaalisten sijoittajien käyttäytymisen vaikutus arvopapereiden hintoihin
Keywords: Investor Sentiment; Google Search Volumes; Stock Market Return; Size Premium; Nordic Financial Electricity Market; Overconfidence; Exante Option Pricing; sijoittajat; markkinointi; hinnat; rahoitus; arvopaperit; arvopaperimarkkinat; sijoitukset; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|